Everyday nationalism : women of the Hindu right in India - Menon, Kalyani Devaki (Ethnography of political violence., 2010)
This ethnography analyzes the popularity of Hindu nationalism in contemporary India through examining the everyday acts of women activists, finding that women's ability to recruit individuals from a variety of backgrounds and the movement's willingness to accommodate a multiplicity of positions are central to understanding its expansionary power.